An automatic modelling strategy for the reverse engineering of wrap-around freeform surfaces. (31st July 2008) - Sun, Y.W.; Guo, D.M.; Jia, Z.Y.
In this paper, a modelling strategy is proposed for the reverse engineering of wrap-around freeform surfaces. The method only needs to manually select four boundary corner points from sampled points. Then sampled points are converted into 2D data points based on the viewpoint principle. Four boundaries of the planar point set are automatically extracted by using a boundary-tracing algorithm. A bilinear coons surface is subsequently established with the given curved boundaries. As a result, the parameterisation of sampled points is gained after thinning data points. Experimental results are finally given to testify the feasibility of the proposed approach.